Journal of Optical Communications (De Gruyter, 1980)
This is the journal for all scientists working in optical communications. JOC was the first international publication covering all fields of optical communications with guided waves. It is the aim of the journal to serve all scientists engaged in optical communications as a comprehensive journal tailored to their needs and as a forum for their publications. The journal focuses on the main fields in optical communications.